The Interferences of Sasak Language on English Vocabulary Mastery - Sugianto Sugianto; Kamarudin Kamarudin (Universitas Pendidikan Mandalika, 2021)
The article is aimed at revealing some crucial languags interferences that happened to Sasak students who were learning English. The Sasak itself is a sub-Austronesian language spoken by most citizens who live in Lombok and half of western Sumbawa. These language interferences play very important roles either in helping the students mastering eng English or challenging them. The positive interferences brought easiness to the students of Sasak to master English vocabularies. On the other hand, the negative interferences caused difficulties for students to learn English as their second language.The article say that defining the language interferences between Sasak and English brought some positive effects, particularly it is a real endeavor to help the lecturers, teachers, and instructors of English in conducting the teaching and learning practices. The research was conducted for the sake of findingpieces of evidences of these interferences issues. The interview was conducted by involving Sasak students who were learning English. Moreover, a writing test of vocabulary was also conducted to confirm the existance of language interferences when they are producing English words. Went through the research, it was concluded that some morphemes that exited in the Sasak were a lot similar to morphemes existed in English. Positively, this fact brought good effects on students who were learning English. Unfortunately, the accent in pronouncing those words was completely different, which then challenged the students to master the English vocabularies.